Establishing a methodology to study the influence of quercetin on the metabolism of the K562/aDM cell line using nuclear magnetic resonance technology. (2015) - , Xi Xia; , Changli Shao; , Qian Liu; Cai, Tiange; Cai, Yu
No abstract available